The relationship between work-related social media use and work-life integration among generation Z employees in Indonesia - Laura Aurelia Austine Untung; Zamralita Zamralita; Jessica Jessica (Priviet Social Sciences Journal, 2026)
The use of work-related social media by Generation Z has become a widespread phenomenon, creating a dilemma between flexibility and the blurring of boundaries between professional and personal lives. As digital natives, they are expected to seamlessly integrate work and personal life; however, they are also vulnerable to technostress. This study examines the relationship between Work-Related Social Media Use (WSMU) and Work-Life Integration (WLI) among Generation Z employees. This study adopts Boundary Theory and the Job Demands-Resources model as its theoretical framework. A correlational quantitative approach was employed, involving 203 Generation Z employees selected through convenience sampling method. Data were collected using the Work-Life Boundary Enactment Scale and Work-Related Social Media Questionnaire. The results of the correlation analysis rejected the initial hypothesis. A highly significant negative relationship was found between WSMU and WLI (r = -0.206, P = 0.003). This suggests that employees who effectively utilize social media for work tend to enact stronger segmentation strategies rather than integration. Further analysis revealed that hybrid workers reported significantly higher integration levels than office-based workers, and female employees engaged in more productive WSMU behaviors.